Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1039/d1ra05580a
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics and mechanism of H2O2 decomposition at the U3O8 surface in bicarbonate solution

Abstract: A transition from catalytic to oxidative H2O2 decomposition on U3O8 was observed with NaHCO3 with significant implications for uranium dissolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The calculated values of k were in the range 0.5 to 63 × 10 −3 s −1 m −2 . A previous study by the authors 12 investigating U dissolution from U 3 O 8 in bicarbonate solution at 25 °C showed measured k values between 0.7 and 2.7 × 10 −4 s −1 m −2 , indicating that H 2 O 2 decomposition is slower on more oxidised forms of U. This effect is likely to be due to the abundance of U IV in UO 2 relative to U 3 O 8 facilitating the oxidative decomposition of H 2 O 2 at the surface via eqn (4) and (5 ).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The calculated values of k were in the range 0.5 to 63 × 10 −3 s −1 m −2 . A previous study by the authors 12 investigating U dissolution from U 3 O 8 in bicarbonate solution at 25 °C showed measured k values between 0.7 and 2.7 × 10 −4 s −1 m −2 , indicating that H 2 O 2 decomposition is slower on more oxidised forms of U. This effect is likely to be due to the abundance of U IV in UO 2 relative to U 3 O 8 facilitating the oxidative decomposition of H 2 O 2 at the surface via eqn (4) and (5 ).…”
Section: Resultsmentioning
confidence: 80%
“…The structure of the UO 2 powder was confirmed by XRD according to the procedure previously described in ref. 12 . An average crystallite size of 62 nm was obtained, with a cubic lattice constant of 5.46 Å which is consistent with published data for UO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation